МЕТОД СЛАБОЙ АППРОКСИМАЦИИ ДЛЯ ЗАДАЧИ КОШИ ДЛЯ ОДНОМЕРНОЙ СИСТЕМЫ УРАВНЕНИЙ ТИПА БЮРГЕРСА ВОЗНИКАЮЩЕЙ В ДВУХСКОРОСТНОЙ ГИДРОДИНАМИКЕ - Турдиев, У.Қ. (SCIENCE and SOCIETY, 2022)
The Koshi problem for a one-dimensional system of Byurgers type equations arising in two-velocity hydrodynamics is considered. By the method of weak approximation, the existence and uniqueness of the solution of the Koshi problem for a one-dimensional Byurgers type system is proved.
Keywords: two-velocity hydrodynamics; Byurgers type system; weak approximation method; Cauchy problems; linear equations; function